Effect of glycation degree on the in vitro simulated gastrointestinal digestion: A promising formulation for egg white gel with controlled digestibility. (1st July 2021) - Yang, Meng; Liu, Jingbo; Yang, Xiaohan; Li, Shoulu; Li, Chuang; Liu, Boqun; Ma, Sitong; Liu, Xuanting; Du, Zhiyang; Zhang, Ting; Yu, Yiding
Highlights: EWG with higher glycation degree shows better gelation and lower digestibility. Glycation preference for ovotransferrin is important to regulate gel structure. Binding disorder and steric hindrance could ascribe to lower digestibility. Gel structure was predominant over amino acids modification for digestibility. Abstract: The mechanism between food gelation and its digestibility has attracted increasing attention over the past few decades. This study aimed to evaluate the effect of glycation degree on the gelation and digestibility of egg white gel (EWG) using an in vitro model and a multi-scale characterization of gel structure. Results showed that EWG glycated with increasing d -ribose by covalent bonds exhibited better gelling properties and lower in vitro digestibility according to the appearance of soluble proteins and peptides. Besides, glycation preference for ovotransferrin at lysine might be important for regulating gel structure and proteolysis accessibility via the ratio of fibrous and granular aggregates. Moreover, gel structure was predominant over amino acids modification for digestibility. Binding disorder and steric hindrance could ascribe to the lower digestibility of gels. These findings are enlightening for the formulation and production of food matrix with controlled digestibility through glycation in food and related pharmaceutical fields.